A new genus for four myobatrachid frogs from the South Western Australian Ecoregion - Webster, Grant N.; Bool, Ian (Zootaxa, 2022)
The southern Australian endemic genus Geocrinia Blake 1973 (Anura: Myobatrachidae) currently contains seven species, with five restricted to Western Australia and two in the south-eastern states covering parts of New South Wales, Victoria, Tasmania and South Australia. All species have a modified life history with at least some or all of the larval stage being completed terrestrially. Four of the Western Australian species have terrestrial, non-feeding tadpoles nourished by yolk until metamorphosis. The remaining species have a biphasic development with embryos developing on land followed by an aquatic tadpole stage. The presence of species groups within the Geocrinia has been recognised since the 1970s, with all relevant subsequent studies supporting a model of two groups within the genus, recovered as reciprocally monophyletic in phylogenetic analyses. We examined character traits of the seven recognised Geocrinia species, concluding that distinction of the two monophyletic groups is supported by differences in life history strategy, larval morphology, adult morphology, call structure, breeding season and geographic distribution. The differences between the two groups correspond to phylogenetic structuring for all traits except distribution. Given reciprocal monophyly, and greater variation in traits than present within other myobatrachid genera, we conclude that the two groups should be given generic distinction. We therefore describe a new genus, Anstisia gen. nov., for four Western Australian Geocrinia species, retaining three species in Geocrinia. This increases the number of recognised myobatrachid genera to 14: five are endemic to south-western Australia.